Lawanen mga alaala ng pagkubkob : mga haraya ng pag-igpaw - Tiburon, Almayrah Abbas; Cura, Faye; Rival, Rae; Gantala Press (Lungsod Makati, Pilipinas Gantala Press, 2018)
Collection of literary works on result of the military action in Marawi, Philippines.
In Tagalog, and some works in English and Maranao.
UCWS-3446g donated by Gantala Press, Inc. - August 2019
Keywords: Marawi, Battle of, Marawi, Philippines, 2017.; Marawi (Philippines) -- History; Marawi (Philippines) -- Social conditions